MAKASSAR CITY GOVERNMENT PERFORMANCE IN HANDLING CASES OF SEXUAL VIOLANCE AGAINST CHILDREN - Nawir Rahman; Syamsu Rijal; Askar Askar; Risma Niswaty; Sitti Hardiyanti Arhas (Sosiohumaniora, 2022)
This study aims to find out how the performance of the Regional Technical Implementation Unit for the Protection of Women and Children in handling cases of sexual violence against children in Makassar City, besides that this study will also describe how to handle sexual violence around the world. The research method used is a descriptive method using a qualitative approach with data collection techniques through observation, interviews, and documentation. Data analysis uses miles, huberman, and saldana models consisting of data condensation, data presentation and inference. Performance as a public bureaucracy is supported by human resources from various fields so as to be able to develop programs that support organizational performance that cannot be separated from sops based on security guarantees